Kidney transplant outcomes in recipients with visual, hearing, physical and walking impairments: a prospective cohort study. Issue 7 (14th August 2019) - Thomas, Alvin G; Ruck, Jessica M; Chu, Nadia M; Agoons, Dayawa; Shaffer, Ashton A; Haugen, Christine E; Swenor, Bonnielin; Norman, Silas P; Garonzik-Wang, Jacqueline; Segev, Dorry L; McAdams-DeMarco, Mara
Abstract: Background: Disability in general has been associated with poor outcomes in kidney transplant (KT) recipients. However, disability can be derived from various components, specifically visual, hearing, physical and walking impairments. Different impairments may compromise the patient through different mechanisms and might impact different aspects of KT outcomes. Methods: In our prospective cohort study (June 2013–June 2017), 465 recipients reported hearing, visual, physical and walking impairments before KT. We used hybrid registry-augmented Cox regression, adjusting for confounders using the US KT population (Scientific Registry of Transplant Recipients, N  = 66 891), to assess the independent association between impairments and post-KT outcomes [death-censored graft failure (DCGF) and mortality]. Results: In our cohort of 465 recipients, 31.6% reported one or more impairments (hearing 9.3%, visual 16.6%, physical 9.1%, walking 12.1%). Visual impairment was associated with a 3.36-fold [95% confidence interval (CI) 1.17–9.65] higher DCGF risk, however, hearing [2.77 (95% CI 0.78–9.82)], physical [0.67 (95% CI 0.08–3.35)] and walking [0.50 (95% CI 0.06–3.89)] impairments were not. Walking impairment was associated with a 3.13-fold (95% CI 1.32–7.48) higher mortality risk, however, visual [1.20 (95% CI 0.48–2.98)], hearing [1.01 (95% CI 0.29–3.47)] and physical [1.16 (95% CI 0.34–3.94)] impairments were not. Conclusions: Impairments are common among KT recipients, yet only visual impairment and walking impairment are associated with adverse post-KT outcomes. Referring nephrologists and KT centers should identify recipients with visual and walking impairments who might benefit from targeted interventions pre-KT, additional supportive care and close post-KT monitoring.